Presentations for Introducing the new Women’s Empowerment Metric for National Statistical Systems (WEMNS) - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Heckert, Jessica; Seymour, Greg (International Food Policy Research Institute, 2024)
The new Women’s Empowerment Metric for National Statistical Systems (WEMNS) is a streamlined tool for measuring women’s empowerment, intended for use in large-scale, multitopic surveys conducted by national statistical systems. WEMNS is designed to measure empowerment in households with all types of livelihoods, in both urban and rural areas, complementing the Women’s Empowerment in Agriculture Index (WEAI), which focuses on agricultural households. WEMNS was developed by the International Food Policy Research Institute (IFPRI), Emory University, Oxford University, and the World Bank’s Living Standards Measurement Study Unit in collaboration with country partners and the 50x2030 Initiative, supported by the Bill & Melinda Gates Foundation and the United States Agency for International Development.